Promising nanotherapy in treating leishmaniasis - de Souza, Aline; Marins, Débora Soares Souza; Mathias, Samir Leite; Monteiro, Lis Marie; Yukuyama, Megumi Nishitani; Scarim, Cauê Benito [UNESP]; Löbenberg, Raimar; Bou-Chacra, Nádia Araci (Elsevier, 2018)
Leishmaniases are infectious diseases caused by an intracellular protozoan in humans by 20 different species of Leishmania among more than 53 species. There are at least twelve million cases of infections worldwide and three hundred and fifty million people are at risk in at least 98 developing countries in Africa, South-East Asia, and the Americas. Only Brazil presented high burden for both visceral leishmaniasis (VL) and cutaneous (CL). Chemotherapy is the main means of dealing with this infection. Nevertheless, only a few effective drugs are available, and each has a particular disadvantage; toxicity and long-term regimens compromise most chemotherapeutic options, which decreases patient compliance and adherence to the treatment and consequently the emergence of drug-resistant strains. Nano drug delivery systems (NanoDDS) can direct antileishmanial drug substances for intracellular localization in macrophage-rich organs such as bone marrow, liver, and spleen. This strategy can improve the therapeutic efficacy and reduce the toxic effects of several antileishmanial drug substances. This review is an effort to comprehensively compile recent findings, with the aim of advancing understanding of the importance of nanotechnology for treating leishmaniases.
Keywords: Drug delivery systems; Drug targeting; Human leishmaniasis; Nanotechnology; Nanotherapeutics; Treatment